2017
DOI: 10.1049/iet-nbt.2017.0044
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterisation and potential biomedical applications of magnetic core–shell structures: carbon‐, dextran‐, SiO 2 ‐ and ZnO‐coated Fe 3 O 4 nanoparticles

Abstract: Due to the strong effect of nanoparticles' size and surface properties on cellular uptake and bio-distribution, the selection of coating material for magnetic core-shell nanoparticles (CSNPs) is very important. In this study, the effects of four different biocompatible coating materials on the physical properties of Fe 3 O 4 (magnetite) nanoparticles (NPs) for different biomedical applications are investigated and compared. In this regard, magnetite NPs are prepared by a simple co-precipitation method. Then, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 43 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…Taking advantage of the fact that Fe 3+ ions are acid-leaching, while Si 4+ ions are base-leaching, the two ions were selectively isolated from a roasted drinking water treatment sludge, otherwise a pollutant for waterbodies, in a study from 2016 and used as precursors for the synthesis of silica-coated iron oxide particles, which would then go on and be tested for the adsorption and separation of other sorbates . A parallel study on carbon- and silica-coated iron oxide nanoparticles from 2018 demonstrated higher specific saturation magnetization values for the former and a higher coercivity for the latter, suggesting their potential in application as MRI contrast agents and hyperthermia agents, respectively . A year later, it was shown that the confinement of iron oxide nanoparticles under a layer of nitrogen-doped graphitic carbon facilitates the adsorption of oxygen onto carbon and reduces the energy of OOH group formation, this rendering carbon a more effective catalyst for the oxygen reduction reaction .…”
Section: Biphasic Carbon-coated Iron (Oxide) Compositionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking advantage of the fact that Fe 3+ ions are acid-leaching, while Si 4+ ions are base-leaching, the two ions were selectively isolated from a roasted drinking water treatment sludge, otherwise a pollutant for waterbodies, in a study from 2016 and used as precursors for the synthesis of silica-coated iron oxide particles, which would then go on and be tested for the adsorption and separation of other sorbates . A parallel study on carbon- and silica-coated iron oxide nanoparticles from 2018 demonstrated higher specific saturation magnetization values for the former and a higher coercivity for the latter, suggesting their potential in application as MRI contrast agents and hyperthermia agents, respectively . A year later, it was shown that the confinement of iron oxide nanoparticles under a layer of nitrogen-doped graphitic carbon facilitates the adsorption of oxygen onto carbon and reduces the energy of OOH group formation, this rendering carbon a more effective catalyst for the oxygen reduction reaction .…”
Section: Biphasic Carbon-coated Iron (Oxide) Compositionsmentioning
confidence: 99%
“…226 A parallel study on carbon-and silica-coated iron oxide nanoparticles from 2018 demonstrated higher specific saturation magnetization values for the former and a higher coercivity for the latter, suggesting their potential in application as MRI contrast agents and hyperthermia agents, respectively. 227 A year later, it was shown that the confinement of iron oxide nanoparticles under a layer of nitrogen-doped graphitic carbon facilitates the adsorption of oxygen onto carbon and reduces the energy of OOH group formation, this rendering carbon a more effective catalyst for the oxygen reduction reaction. 228 Another study from 2019 demonstrated a 33% reduction in surfactant adsorption in the porous media due to the use of carbon-coated iron nanoparticles and the potential for use in oil recovery at reservoir conditions.…”
Section: Biphasic Carbon-coated Iron (Oxide) Compositionsmentioning
confidence: 99%